Fresno County Bar Association Luncheon with Justice Cruz Reynoso - Watkins, Howard::::::::: (1982)
Lenore Schreiber, Justice Reynoso speaking, Fresno County Bar Association President-Elect Doug Jensen, Thomas Tusan The Fresno Hilton signs on lectern